Features of the Formation of Humoral Immunity in Individuals with Various Clinical Manifestations of COVID-19 - T. A. Platonova; A. A. Golubkova2; E. A. Karbovnichaya; S. S. Smirnova (Эпидемиология и вакцинопрофилактика)
Relevance In the context of the new coronavirus infection (COVID-19) pandemic, research on the formation of an immune response to SARS-CoV-2 in patients with various clinical forms of this infection is of particular relevance, which is important for understanding the degree of their participation in the formation of population immunity and assessing individual immunity to SARS-CoV-2 in the future. Aim of the study was to analyze the timing of the formation of specific antibodies to SARS-CoV-2 and the duration of their preservation in patients with a new coronavirus infection. Materials and methods. The timing of the formation of specific antibodies of three classes (IgA, IgM and IgG) to SARS-CoV-2 in 218 patients was evaluated in the first days of the disease. Subsequently, they were re-examined at various times from the onset of the disease, from one to four times (a total of 321 control points). To assess the duration of preservation of antibodies to COVID-19 in patients who were ill, a prospective study was organized, in which 368 people participated. Screening for specific class G antibodies was performed every 2–4 weeks, within one to eight months of the onset of clinical manifestations of COVID-19. In total 919 control points. The antibodies were examined by solid-phase enzyme immunoassay using the SARS-CoV-2IgM-ELISA-BEST and SARS-CoV-2-IgG-ELISA-BEST test systems (manufactured by VECTOR-BEST JSC) and Antigma A (manufactured by Generium). Results. In most of the examined individuals, class M and G antibodies began to form from day 10 of the disease, while class A antibodies were detected from day 5. In mild and asymptomatic forms of coronavirus infection, IgG antibodies to SARS-CoV-2 were not formed in most cases, and seroprotection levels correlated with the severity of the disease. The duration of preservation of IgG antibodies could be at least 8 months, but there were isolated cases of their elimination both after COVID-19 in the form of respiratory infection and after interstitial pneumonia. With continuing problems with COVID-19, there were no cases of recurrent disease among individuals who formed G-antibodies (including those who lost them 4-5 months after the disease) during the follow-up period. Conclusion. Thus, according to the results of the study, important materials were obtained on the peculiarities of the formation of a humoral immune response to a new coronavirus infection. However, to fully understand the immune response to SARS-CoV-2, it is necessary to assess the avidity of IgG antibodies or their ability to neutralizing the virus, as well as to study cellular immunity in patients who have had COVID-19 but have not formed antibodies.